Thermal management of electronics devices with PCMs filled pin-fin heat sinks: a comparison - Arshad, Adeel; Ali, Hafiz Muhammad; Jabbal, Mark; Verdin, P.G. (Elsevier, 2017)
The present paper covers the comparison of two different configurations (square and circular) pinfin heat sinks embedded with two different phase change materials (PCMs) namely paraffin wax and n-eicosane having different thermo-physical properties were carried out for passive cooling of electronic devices. The pin-fins, acting as thermal conductivity enhancers (TCEs), of 2